PENGARUH PROFITABILITAS, SOLVABILITAS, SIZE, KOMITE AUDIT, KOMPLEKSITAS OPERASI DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Yohaniar, Eliana; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to examine the influence of profitability, solvability, audit committee, operation complexity and auditor opinion to the audit delay through the annual financial statement which has been prepared by consumer goods companies which are listed in IDX in 2013-2016 periods. The population of this research has been obtained by using purposive sampling method on consumer goods companies which are listed in IDX in 2013-2016 periods and based on the predetermined criteria there are 34 consumer goods companies which have been selected as samples with 4 consecutive years of observation so 136 observation objects have been obtained. The data is the secondary data in the form of annual financial statement of the company which has been obtained from IDX. The analysis has been carried out by using multiple linear regressions with its significance level is 5% and the application instrument of SPSS. The result of the research shows that the audit committee gives negative influence to the audit delay meanwhile the variables of profitability, solvability, size, operation complexity and auditor opinion does not gives any influence to the audit delay. Simultaneously the independent variables give significant influence to the dependent variable with its significance level is 0.011.Keywords: Audit delay, financial ratio, size, audit committee, auditor opinion.